Penggunaan Media Audio Visual Dalam Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti Di Sekolah Menengah Pertama Negeri 2 Bangli - Diky, Putu Diky; Sutriyanti, Ni Komang; Putra, I Gede Dedy Diana (UHN IGB Sugriwa Denpasar, 2024)
Audio visual media is a tool that has sound and image elements that are used to convey a message, this study focuses on describing the use of audio visual media in learning Hindu religion and character education at SMP Negeri 2 Bangli, with the aim of increasing student interest in learning. Discussed, namely, (1) the form of using audio visual media in learning Hindu religious education and character education, (2) obstacles experienced in the use of audio visual media in learning Hindu religious education and character education, (3) efforts made to overcome obstacles in the use of Audio Visual Media in learning Hindu Religion and Moral Education. This study aims to determine the process of using audio-visual media, the obstacles and efforts made by teachers, students and the school. This problem is studied by using the theory of Cognitive, Convergence and Behaviorism. The research subjects were teachers and students of class VII. This study uses data collection techniques, namely by observation, interviews, documentation studies and literature studies. The data obtained were then analyzed using qualitative descriptive techniques. Based on research and data analysis that (1) the process of using audio-visual media is quite good (2) the obstacles faced in the use of audio-visual media include the constraints of teachers, students and infrastructure, (3) efforts to overcome obstacles to the use of audio-visual media that occur there are three , namely the efforts of teachers, students and the school. It can be understood that the use of audio-visual media in learning Hindu Religion and Moral Education at SMP Negeri 2 Bangli is of good quality based on problem analysis with the theory used in this study. Keywords: Audio visual media, Hindu religious education learning.